The complex path of agro-energy towards sustainability. What role for renewable energy communities? - Lattanzi, Pamela; Isidori, Annachiara (Przegląd Prawa Rolnego, 2024)
The article aims at defining the role that agroenergies play in the EU strategy for energy – as outlined in the Green Deal and updated in the context of the RePowerEU – and, as a consequence, in the Italian legal system, emphasising the need to ensure their sustainability, the key to recreate the relationship between agri-food production and energy production activities. The measures gradually adopted at a European and national level to advance the complex path towards the sustainability of agroenergies, demonstrate the urgency of investing not only in environmental sustainability, but also in economic and social sustainability and, in particular, in (social) food sustainability of agroenergies. From this perspective, a significant contribution comes from renewable energy communities (REC), innovative organisational models that offer interesting opportunities for agri-food operators. In particular, when analysing the role that agricultural producers can play within REC and, at the same time, the contribution that these structures can offer to affirm the sustainability of agroenergies, the potentialities that agroenergies communities provide to the energy and ecological transition process, clearly come to light.